cdc2-like kinase from rat spinal cord specifically phosphorylates KSPXK motifs in neurofilament proteins: isolation and characterization. - Shetty, K T (1993)
A protein kinase that phosphorylates a specific KSP sequence [K(S/T)PXK], which is abundant in high molecular weight neurofilament (NF) proteins, was identified and isolated from rat spinal cord. Characterization of this enzyme activity revealed a close relationship with p34cdc2 kinase with respect to its molecular mass (32.5 kDa by SDS/PAGE) and substrate specificities. It could phosphorylate a synthetic peptide analog of the simian virus 40 large tumor antigen, reportedly a specific substrate for p34cdc2 kinase. Histone (H1) and peptide analogs of the KSP sequence present in the C-terminal end of rat and mouse neurofilament proteins were phosphorylated. This kinase did not phosphorylate alpha-casein and peptide substrates of other known second messenger-dependent or -independent kinases. Dephosphorylated rat NF protein NF-H was strongly phosphorylated by the purified enzyme; NF proteins NF-M and native NF-H, but not NF-L, were slightly phosphorylated. Studies on synthetic peptide analogs of KSP repeats with substitution of specific residues, known to be present in the C-terminal regions of NF-H, revealed a consensus sequence of X(S/T)PXK, characteristic of the p34cdc2 kinase substrate. On Western blots, the enzyme was immunoreactive with antibody against the C-terminal end of cdc2 kinase (mouse) and neuronal cdc2-like kinase from rat but not with an antibody against the conserved PSTAIRE region of the p34cdc2 kinase. The antibody against the C-terminal end of cdc2 kinase could immunoprecipitate (immunodeplete) the purified kinase activity. Since the adult nervous system is composed primarily of postmitotic cells, the present observations indicate a nonmitotic role for this cdc2-like kinase activity. The effective phosphorylation of NF-H by this kinase suggests a function in axonal structure.